2003
DOI: 10.1039/b304072k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anion fluorination in ionic liquids—physical properties of a range of bis(methanesulfonyl)amide salts

Abstract: The bis(trifluoromethanesulfonyl)amide, TFSA, anion is widely used in the genesis of room temperature ionic liquids as it is non-spherical, fluorinated and has a particularly diffuse charge. However, the extent to which each of these structural features is responsible for the low melting point, fluidity and excellent stability of the resultant ionic liquids has yet to be described. We present the synthesis and analysis of a range of analogous, non-fluorinated species containing the bis(methanesulfonyl)amide, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 21 publications
8
119
0
2
Order By: Relevance
“…For example, ILs containing Tf 2 N − offer low viscosity and high electrochemical and thermal stability [45]. If bis(trifluoromethylsulfonyl)amide Tf 2 N − is replaced by bis(methylsulfonyl)amide, viscosity increases and stability decreases [46]. Neutron scattering experiments on crystalline, glassy, and liquid samples of imidazolium ILs have suggested that ILs have an organizational behavior intermediate between isotropic liquids and liquid crystals [31].…”
Section: Ionic Liquids (Ils)mentioning
confidence: 99%
“…For example, ILs containing Tf 2 N − offer low viscosity and high electrochemical and thermal stability [45]. If bis(trifluoromethylsulfonyl)amide Tf 2 N − is replaced by bis(methylsulfonyl)amide, viscosity increases and stability decreases [46]. Neutron scattering experiments on crystalline, glassy, and liquid samples of imidazolium ILs have suggested that ILs have an organizational behavior intermediate between isotropic liquids and liquid crystals [31].…”
Section: Ionic Liquids (Ils)mentioning
confidence: 99%
“…8 In this sense, ILs could be an alternative to organic solvents, because of their lack of vapour pressure, their chemical and thermal stability 9 and their widely tunable properties with regard to polarity, hydrophobicity and solvent miscibility behavior through appropiate modification of the cation and anion. 10,11 They are therefore often referred to as designer solvents. The most commonly used ILs are based on dialkylimidazolium and tetraalkyl ammonium cations combined with anions having a strongly delocalized negative charge (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The density (ρ) of ionic liquids (ILs) decreases with the increase in organic cation bulkiness and anion selection affects ILs' density. Normally, the density of ILs varies in the range of 1.05-1.36 g/cm 3 at ambient temperature [43,44]. In terms of ILs' thermal stability, a research conducted had observed that thermal stability was dependent on both the cation and the anion of ILs.…”
Section: Physicochemical Properties Of Imidazolium-based Ionic Liquidsmentioning
confidence: 99%